2MTO, a new mapping tool to achieve lean benefits in high-variety low-volume job shops. Issue 5 (4th April 2017) - Bertolini, Massimo; Romagnoli, Giovanni; Zammori, Francesco
Abstract: This paper proposes the 'Mapping Tool for Make-To-Order companies' (2MTO), a new approach to map, analyse and achieve lean benefits in high-variety-low-volume job shops. The focus is, mainly, on the transitional phase from push to pull, when there is a compelling need to acquire a deep understanding of the current state of the system under analysis. Sometimes, in this initial phase, a pure pull approach cannot be developed and a job shop configuration must be maintained. If so, 2MTO allows selecting a suitable hybrid Production Planning and Control system to control Work-In-Process and to limit lead times, so as to quickly achieve lean benefits, without significantly altering the original layout. 2MTO is fully explained making reference to an Italian precision mechanic company, where the application of the method led to a successful implementation of a Workload Control system.